The implementation of freedom of speech principles in Indonesian press regulation - Putri Tunjung Sari (International Journal of Communication and Society, 2020)
This paper aims to see the implementation of freedom of speech principles in Indonesian press regulation, because as we have known, this regulation was made in very short period during political change in Indonesia. This change influences the Press Law too. The change in the Press Law which has further facilitated freedom of speech, it turns out to have a big impact on numerous parties, especially journalists and owners of mass media business entities. In this study, the researcher used critical paradigm to see effect of this law and problems those might be came because of the implementation. This study found that the implementation, freedom of speech regulated in the 1999 Press Law often turns out to intersect with the freedom of others so that it needs to be evaluated, reviewed, and revised.